A Simple Gaussian Measurement Bound for Exact Recovery of Block-Sparse Signals. (26th November 2014) - Han, Zhi; Wang, Jianjun; Jing, Jia; Zhang, Hai
Abstract : We present a probabilistic analysis on conditions of the exact recovery of block-sparse signals whose nonzero elements appear in fixed blocks. We mainly derive a simple lower bound on the necessary number of Gaussian measurements for exact recovery of such block-sparse signals via the mixed l 2 / l q ( 0 < q ≤ 1 ) norm minimization method. In addition, we present numerical examples to partially support the correctness of the theoretical results. The obtained results extend those known for the standard l q minimization and the mixed l 2 / l 1 minimization methods to the mixed l 2 / l q ( 0 < q ≤ 1 ) minimization method in the context of block-sparse signal recovery.